The Influence of Perceived Organizational Support and Self-Resilience on Work Engagement among Teachers of Indonesia - Nurfadhilah, Arum; Widiasih, Puti Archianti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The study aims to measure how perceived organizational support and self-resilience affect teacher work engagement in Indonesia. A multiple regression research design using a quantitative approach was used in this study. A total of 400 teachers participated in this study spread across several province in Indonesia. Purposive sampling was the form of sampling used in this study, and was conducted using non-probability techniques based on criteria set by the researcher. The significance value of 0.000 indicates that the research findings show significant results between perceived organizational support and self-resilience with work engagement. Perceived organizational support and self-resilience accounted for 42.8% of the effective contribution of these variables to work engagement, other factors influenced the remaining percentage. This research produces new findings, that the variables of perceived organizational support and resilience when tested together with the variable of work engagement with a sample of teachers have significant results. Therefore, to ensure that teachers have high engagement at work and their efforts positively influence the learning process, it is crucial for schools to be able to maintain a good level of organizational support and it is important for teachers to have good psychological resilience.